Comparison of perventricular and percutaneous ultrasound-guided device closure of perimembranous ventricular septal defects - Huang, Liu Liu; Chen, Mai; Zeng, De Cai; Su, Chun Xiao; Jiang, Chun Lan; Zheng, Bao Shi; Wu, Ji; Li, Shi Kang (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background. Ultrasound-guided percutaneous device closure of perimembranous ventricular septal defects (PmVSD) is a minimally invasive recent treatment approach. Perventricular PmVSD device closure is an emerging radiation-free intervention, yet it comes with certain limitations. No studies compared both of these treatment approaches. Methods. We performed a retrospective institutional data comparison of percutaneous (PCP Group, n=138) and perventricular (PVP Group, n=67) ultrasound-guided device closure procedures in 205 patients with PmVSD between March 2017 and December 2022. Results. Patients of the PCP and PVP groups had a median age of 4.9 years (IQR, 3.1-14.0) and 5.3 years (IQR, 3.4-13.1) respectively. The median PmVSD diameter in the PCP Group was 4.0 mm (IQR, 3.3-5.3) and 5.2 mm (IQR, 4.0-7.0) in the PVP Group (p=0.001). There was no significant difference in success rates between the PCP and PVP Groups (intention-to-treat population, 88.4% vs. 92.5%, p=0.36; as-treated population, 88.4% vs. 89.3%, p=0.84). 5/8 failed percutaneous cases that were shifted to the perventricular approach were successful. Compared to the PVP Group, patients of the PCP group experienced a significant decrease in ventilation time, drainage volume, and postoperative hospital stay (p<0.001). The median follow-up period was 24 months (IQR, 6-42) for the PCP group and 61 months (IQR, 53-65) for the PVP group. The overall severe adverse event rate was 0% in the PCP group and 3.0% in the PVP group. Conclusions. Perventricular and percutaneous ultrasound-guided device closure of PmVSD are both effective and safe treatment options. The percutaneous approach offers less trauma and faster recovery and may be the preferred approach in selected patients.